Therapeutic Effects of an anti-ADAMTS-5 Antibody on Joint Damage and Mechanical Allodynia in a Murine Model of Osteoarthritis - Miller, Rachel E. (Osteoarthritis Cartilage, 2015)
OBJECTIVE: The primary goal of this study was to test the disease-modifying effect of blocking a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-5 with a neutralizing monoclonal antibody (mAb) starting 4 weeks after destabilization of the medial meniscus (DMM) in the mouse. We also investigated whether ADAMTS-5 blockade reversed mechanical allodynia and decreased monocyte chemoattractant protein (MCP)-1 production by dorsal root ganglia (DRG) cells. METHODS: Ten-week old male C57BL/6 mice underwent DMM surgery and were either left untreated or treated with anti-ADAMTS-5 mAb or IgG2c isotype control mAb starting 4 weeks after surgery. Knees were collected for histopathology 4 or 12 weeks later. Mechanical allodynia was monitored biweekly in the ipsilateral hind paw through 16 weeks. DRG were collected and cultured 8 weeks after DMM for analysis of MCP-1 production. RESULTS: By 4 weeks after DMM, mild cartilage degeneration was evident in the medial compartment, small osteophytes were present, and subchondral bone sclerosis was established. By 16 weeks after surgery, significant cartilage deterioration was apparent on the medial tibial plateaux and medial femoral condyles, osteophyte size had increased, and subchondral bone sclerosis was maintained. Treatment with ADAMTS-5 mAb from week 4-16 after surgery slowed cartilage degeneration and osteophyte growth but did not affect subchondral bone sclerosis. Moreover, ADAMTS-5 blockade resulted in temporary reversal of mechanical allodynia, which correlated with decreased MCP-1 production by cultured DRG cells. CONCLUSIONS: This study suggests therapeutic efficacy of an ADAMTS-5 mAb in the DMM model, when therapy starts early in disease.